Pyramiding of disease resistant and heat shock protein genes of chili revealed through tightly linked SSRs for sustainable yield under biotic and abiotic stresses - Chowdhury, Mst Farhana Nazneen; Rafii, Mohd Y.; Ismail, Siti Izera; Ramlee, Shairul Izan; Hosen, Monir; Haque, M. A. (Springer Science and Business Media B.V., 2025)
One of the most significant vegetables grown worldwide is pepper (Capsicum annuum L.). Vegetable breeding has faced significant challenges in improving biotic and abiotic stresses with yield. Among all the biotic and abiotic stresses, remarkable losses were found in pre- and post-harvest conditions. Resistant and tolerant cultivars are seen to be the most effective method of controlling pathogens especially Colletotrichum because chemical treatments have a limited ability to manage these pathogens. On the other hand, heat stress also affects the production and yield of chili. Resistance and tolerance genes to this pathogen and heat tolerant were successfully transferred to the superior chili hybrids that revealed through simple sequence repeats. The application of anthracnose disease resistance and heat tolerance genes can potentially enhance drought tolerance and disease resistance, as demonstrated by our study, stacking these genes in chili plants can improve heat tolerance and disease resistance. For the first time, this study used tightly linked SSRs to enhance yield under stress and dual-trait abiding in capsicum annum. Researcher can be used these simple sequence repeats for next molecular screening of chili genotypes for anthracnose resistant and heat tolerant criteria.